Aplikasi Model Pembelajaran TGT (Teams Games Tournament) Untuk Meningkatkan Hasil Belajar IPS Pada Siswa Kelas IV SD Negeri 12 Palembang - Subadra, Desi; Agustina, Rizky; Martita, Faulin (Yayasan Sembilan Pemuda Indonesia, 2023)
This research aims to improve the social studies learning achievement of fourth grade students at SD Negeri 12 Palembang by using the Teams Games Tournament (TGT) learning model, classroom action research on 31 fourth grade students who were used as research objects. It turns out that the Teams Games Tournament (TGT) model can improve learning achievement. social studies students. This can be seen from the increase in the average value of the pre-cycle, cycle I and cycle II. In the pre-cycle, only 4 students passed the KKM with average social studies score of 38.83 or 13%. In cycle I, 21 students passed the KKM with an average score of 70.64 or 67.74%. Meanwhile, in cycle II, 25 students passed the KKM with an average score of 79.03 or 80.64%. And this shows that cycle II has been successful or complete because it has achieved the expected classical KKM of 80%.